Covalent Bisfunctionalization of Two-Dimensional Molybdenum Disulfide - Chen, Xin; Bartlam, Cian; Lloret Segura, Vicente Josep; Moses Badlyan, Narine; Wolff, Stefan; Gillen, Roland; Stimpel-Lindner, Tanja; Maultzsch, Janina; Duesberg, Georg S.; Knirsch, Kathrin; Hirsch, Andreas (Angewandte Chemie International Edition, 2021)
Covalent functionalization of two-dimensional molybdenum disulfide (2D MoS2) holds great promise in developing robust organic-MoS2 hybrid structures. Herein, for the first time, we demonstrate an approach to building up a bisfunctionalized MoS2 hybrid structure through successively reacting activated MoS2 with alkyl iodide and aryl diazonium salts. This approach can be utilized to modify both colloidal and substrate supported MoS2 nanosheets. We have discovered that compared to the adducts formed through the reactions of MoS2 with diazonium salts, those formed through the reactions of MoS2 with alkyl iodides display higher reactivity towards further reactions with electrophiles. We are convinced that our systematic study on the formation and reactivity of covalently functionalized MoS2 hybrids will provide some practical guidance on multi-angle tailoring of the properties of 2D MoS2 for various potential applications.
CRIS-Team WoS Importer:2021-05-14

Effect of TCNQ Layer Cover on Oxidation Dynamics of Black Phosphorus - Meingast, Laura; Kolesnik-Gray, Maria; Siebert, Martin; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Krstic, Vojislav (Physica Status Solidi-Rapid Research Letters, 2018)
The puckered surface of black phosphorus represents an ideal substrate for an unconventional arrangement of physisorbed species and the resulting specific two-dimensional chemistry of this system. This opens the way to investigate the chemical and physical properties of locally confined areas of black phosphorus without the necessity for further physical downscaling of the material. We have evaporated tetracyanoquinodimethane (TCNQ) on top of black phosphorus under over-saturation non-equilibrium conditions in vacuum. The evolution of linear density and height of droplets formed through oxidation during exposure to air is studied time dependently by scanning-force microscopy. Our study suggests that the TCNQ molecules spontaneously arrange in a thin layer of the order of a few nm height, which, however, is fragmented with a periodicity of about 100nm. It is shown that within the confined space separating the layer fragments the chemical dynamics of the oxidation process is remarkably different than on a bare black phosphorus surface.
Keywords: black phosphorus; dynamics; oxidation; TCNQ

Effect of TCNQ Layer Cover on Oxidation Dynamics of Black Phosphorus - Meingast, Laura; Kolesnik-Gray, Maria; Siebert, Martin; Abellán, Gonzalo; Wild, Stefan; Lloret, Vicent; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas; Krstic, Vojislav (Physica Status Solidi-Rapid Research Letters, 2018)
Keywords: Dynamics; Oxidation; Black phosphorus; TCNQ

Electronic Properties of Air-Sensitive Nanomaterials Probed with Microwave Impedance Measurements - Márkus, Bence G.; Csösz, Gábor; Sági, Olivér; Gyüre-Garami, Balázs; Lloret Segura, Vicente Josep; Wild, Stefan; Abellan Saez, Gonzalo; Nemes, Norbert M.; Klupp, Gyöngyi; Kamarás, Katalin; Hirsch, Andreas; Hauke, Frank; et al. (physica status solidi (b), 2018)
Characterization of electronic properties of novel materials is of great importance for exploratory materials development and also for the discovery of new correlated phases. As several novel compounds are available in powder form only, contactless methods, which also work on air-sensitive samples, are highly desired. We present that the microwave cavity perturbation technique is a versatile tool to study conductivity in such systems. The examples include studies on semiconducting-metallic crossover in carbon nanotubes upon alkali doping, study of vortex motion in the K3C60 superconductor, and the characterization of various alkali atom doped phases of black phosphorus.
Keywords: microwave conductivity; black phosphorus; carbon nanotubes; fullerides; intercalation

Exploring the Formation of Black Phosphorus Intercalation Compounds with Alkali Metals - Abellan Saez, Gonzalo; Neiß, Christian; Lloret Segura, Vicente Josep; Wild, Stefan; Chacón-Torres, Julio C.; Werbach, Katharina; Fedi, Filippo; Shiozawa, Hidetsugu; Görling, Andreas; Peterlik, Herwig; Pichler, Thomas; Hauke, Frank; et al. (Angewandte Chemie International Edition, 2017)
Keywords: alkali metals; black phosphorus; DFT calculations; intercalation compounds; Raman spectroscopy

Few layer 2D pnictogens catalyze the alkylation of soft nucleophiles with esters - Lloret Segura, Vicente Josep; Angel Rivero-Crespo, Miguel; Alejandro Vidal-Moya, Jose; Wild, Stefan; Domenech-Carbo, Antonio; Heller, Bettina; Shin, Sunghwan; Steinrück, Hans-Peter; Maier, Florian; Hauke, Frank; Varela, Maria; Hirsch, Andreas; et al. (Nature Communications, 2019)
Group 15 elements in zero oxidation state (P, As, Sb and Bi), also called pnictogens, are rarely used in catalysis due to the difficulties associated in preparing well-structured and stable materials. Here, we report on the synthesis of highly exfoliated, few layer 2D phosphorene and antimonene in zero oxidation state, suspended in an ionic liquid, with the native atoms ready to interact with external reagents while avoiding aerobic or aqueous decomposition pathways, and on their use as efficient catalysts for the alkylation of nucleophiles with esters. The few layer pnictogen material circumvents the extremely harsh reaction conditions associated to previous superacid-catalyzed alkylations, by enabling an alternative mechanism on surface, protected from the water and air by the ionic liquid. These 2D catalysts allow the alkylation of a variety of acid-sensitive organic molecules and giving synthetic relevancy to the use of simple esters as alkylating agents.
CRIS-Team WoS Importer:2019-02-21

Few-layer Black Phosphorous Catalyzes Radical Additions to Alkenes Faster than Low-valence Metals - Tejeda-Serrano, Maria; Lloret, Vicent; Markus, Bence G.; Simon, Ferenc; Hauke, Frank; Hirsch, Andreas; Domenech-Carbo, Antonio; Abellán, Gonzalo; Leyva-Perez, Antonio (ChemCatChem, 2020)
The substitution of catalytic metals by p-block main elements has a tremendous impact not only in the fundamentals but also in the economic and ecological fingerprint of organic reactions. Here we show that few-layer black phosphorous (FL-BP), a recently discovered and now readily available 2D material, catalyzes different radical additions to alkenes with an initial turnover frequency (TOF0) up to two orders of magnitude higher than representative state-of-the-art metal complex catalysts at room temperature. The corresponding electron-rich BP intercalation compound (BPIC) KP6 shows a nearly twice TOF0 increase with respect to FL-BP. This increase in catalytic activity respect to the neutral counterpart also occurs in other 2D materials (graphene vs. KC8) and metal complex catalysts (Fe-0 vs. Fe2- carbon monoxide complexes). This reactive parallelism opens the door for cross-fertilization between 2D materials and metal catalysts in organic synthesis.
CRIS-Team WoS Importer:2020-03-10

Improving Oxygen Reduction Reaction ORR Fuel Cell Efficiency with Carbon Nano Onions - Steiger, Florian; Kaiser, Pascal; Assebban, M'hamed; Hirsch, Andreas; Abellan, Gonzalo; Echegoyen, Luis; Mayrhofer, Karl J. J.; Cherevko, Serhiy; Perez-Ojeda Rodriguez, Maria Eugenia; Lloret Segura, Vicente Josep (243rd ECS Meeting with the Eighteenth International Symposium on Solid Oxide Fuel Cells, 2023)
Hydrogen Fuel cell innovations are cutting-edge clean power solutions highly demanded nowadays. Since the oxygen reduction reaction (ORR) in fuel cells needs to be catalyzed heterogeneously, conductive substrates such as carbon materials are critical for the construction of electrocatalysts. Thus far, the research has been focused on commercially available carbon supports such as the well-known Vulcan, and the high-surface area Ketjenblack.[1] Thanks to the fast development of material science, other carbon supports such as graphite, graphene oxide, and carbon nanotubes have been also studied in a lesser extent, mainly due to their novelty and underdeveloped scale up syntheses.[2,3] This work focuses on utilizing a relatively new and, as of yet, largely unexplored carbon nanomaterial: carbon nano onions (CNOs). CNOs are spherical nanoparticles of about 5 nm diameter composed of concentrical multi-layered fullerenes, first discovered by Ugarte in 1992. CNOs exhibit outstanding properties such as low density, high thermal stability, and a graphitic multilayer morphology, which makes them excellent candidates for a wide variety of applications. Furthermore, the onion's large surface area and high conductivity make them particularly interesting as catalyst support for electrochemical applications as they have already been demonstrated to be a superior Pt support alternative thanks to a higher cycling stability compared to carbon black, since their particle size and morphology suppress catalyst agglomeration and avoid its ripening.[4] However, despite their excellent long-term stability, the few available studies using CNOs were performed using the rotatory disc electrode (RDE) method, reaching only modest performance in the mA / cm2 range. Thus, our work aims to further extend upon this research by measuring the ORR performance with a gas diffusion electrode (GDE), to reproduce realistic fuel cell conditions.[5] The catalyst layer, obtained by growing Pt nanoparticles on CNOs, is characterized by electrochemical measurements such as ORR polarization curves, electrochemical active surface area (ECSA) by the CO-stripping method, and O2-mass transport. The utilization of GDE cells allows for higher current densities and a realistic catalyst mass transport compared to the RDE method, thus better representing an applied ORR fuel cell test.[

Isomerically Pure Star-Shaped Triphenylene-Perylene Hybrids Involving Highly Extended π-Conjugation - Nuin Pla, Neus Edurne; Lloret Segura, Vicente Josep; Amsharov, Konstantin; Hauke, Frank; Abellan Saez, Gonzalo; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Keywords: Graphene; Isomers; Noncovalent functionalization; Perylene; π conjugation

Lattice Opening upon Bulk Reductive Covalent Functionalization of Black Phosphorus - Wild, Stefan; Fickert, Michael; Mitrovic, Aleksandra; Lloret Segura, Vicente Josep; Neiß, Christian; Alejandro Vidal-Moya, Jose; Angel Rivero-Crespo, Miguel; Leyva-Perez, Antonio; Werbach, Katharina; Peterlik, Herwig; Grabau, Mathias; Wittkämper, Haiko; et al. (Angewandte Chemie International Edition, 2019)

Liquid phase exfoliation of carbonate-intercalated layered double hydroxides - Carrasco, Jose; Harvey, Andrew; Hanlon, Damien; Lloret Segura, Vicente Josep; McAteer, Dave; Sanchis-Gual, Roger; Hirsch, Andreas; Hauke, Frank; Abellan Saez, Gonzalo; Coleman, Jonathan N.; Coronado, Eugenio (Chemical Communications, 2019)
Direct exfoliation of a carbonate layered double hydroxide (LDH) has been achieved by using a novel horn-probe sonic tip, avoiding the development of time-consuming anion-exchange reactions. The most suitable solvents were chosen based on the Hildebrand solubility parameters and the thickness of the exfoliated nanosheets confirmed unambiguously the successful delamination.

Monolayer black phosphorus by sequential wet-chemical surface oxidation - Wild, Stefan; Lloret, Vicent; Vega-Mayoral, Victor; Vella, Daniele; Nuin, Edurne; Siebert, Martin; Kolesnik-Gray, Maria; Loeffler, Mario; Mayrhofer, Karl J. J.; Gadermaier, Christoph; Krstic, Vojislav; Hauke, Frank; et al. (RSC Advances, 2019)
We report a straightforward chemical methodology for controlling the thickness of black phosphorus flakes down to the monolayer limit by layer-by-layer oxidation and thinning, using water as solubilizing agent. Moreover, the oxidation process can be stopped at will by two different passivation procedures, namely the non-covalent functionalization with perylene diimide chromophores, which prevents the photooxidation, or by using a protective ionic liquid layer. The obtained flakes preserve their electronic properties as demonstrated by fabricating a BP field-effect transistor (FET). This work paves the way for the preparation of BP devices with controlled thickness.
CRIS-Team WoS Importer:2019-02-21

Noncovalent Functionalization and Passivation of Black Phosphorus with Optimized Perylene Diimides for Hybrid Field Effect Transistors - Lloret, Vicent; Nuin, Edurne; Kohring, Malte; Wild, Stefan; Löffler, Mario; Neiß, Christian; Krieger, Michael; Hauke, Frank; Görling, Andreas; Weber, Heiko B.; Abellán, Gonzalo; Hirsch, Andreas (Advanced Materials Interfaces, 2020)
Amongst the different existing methods to passivate black phosphorus (BP) from environmental degradation, the noncovalent functionalization with perylene diimides (PDI) has been postulated as one of the most promising routes because it allows preserving its electronic properties. This work describes the noncovalent functionalization and outstanding environmental protection of BP with tailor made PDI having peri-amide aromatic side chains, which include phenyl and naphthyl groups, exhibiting a significantly increased molecule-BP interaction. These results are rationalized by density functional theory (DFT) calculations showing that the adsorption energies are mainly governed by van der Waals (vdW) interactions and increase concomitantly with the aromatic character of the side chains. The resulting hybrids are thoroughly characterized showing enhanced ambient and thermal stabilities. Last but not least, hybrid organic–inorganic BP-PDI field effect transistors (FETs) are studied for the first time showing the usefulness of PDI derivatives as efficient passivation layers while obtaining improved values of electron mobilities. These results pave the way for the use of optimized PDIs by molecular engineering to preserve the electronic properties of BP FETs, using straightforward wet chemical approaches.
CRIS-Team Scopus Importer:2020-10-16
Keywords: black phosphorus; noncovalent functionalization; organic field effect transistors; perylene diimides

Noncovalent Functionalization of Black Phosphorus - Abellan Saez, Gonzalo; Lloret Segura, Vicente Josep; Mundloch, Udo; Marcia, Mario; Neiß, Christian; Görling, Andreas; Varela, Maria; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie-International Edition, 2016)
Black phosphorus (BP) was functionalized with organic moieties on the basis of liquid exfoliation. The treatment of BP with electron-withdrawing 7,7,8,8-tetracyano-p-quinodimethane (TCNQ) led to electron transfer from BP to the organic dopant. On the other hand, the noncovalent interaction of BP with a perylene diimide was mainly due to van der Waals interactions but also led to considerable stabilization of the BP flakes against oxygen degradation.
Keywords: Black phosphorus; Charge transfer; Functionalization; Noncovalent interactions; Stability

Topology-Driven Reductive Silylation of Synthetic Carbon Allotropes - Knirsch, Kathrin; Hof, Ferdinand; Lloret Segura, Vicente Josep; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2016)

Unconventional conductivity increase in multilayer black phosphorus - Kolesnik-Gray, Maria; Meingast, Laura; Siebert, Martin; Unbehaun, Tim; Huf, Tobias; Ellrott, Günter; Abellan Saez, Gonzalo; Wild, Stefan; Lloret Segura, Vicente Josep; Mundloch, Udo; Schwarz, Julian; Niebauer, Michael; et al. (npj 2D Materials and Applications, 2023)
Multilayers of so-called 2D van der Waals materials have gained considerable attention as active components of next-generation electronic and optoelectronic technologies, with semiconducting black phosphorus (BP) regarded as one of the most promising systems. The applicability and performance limits of BP in both stand-alone and heterostructure-based multilayer devices are determined by individual flake charge transport properties, which synergistically depend on the number of layers and the strength of interlayer coupling between those. In this work, we study the DC electrical transport characteristics of high-quality BP field-effect devices within a wide range of flake thicknesses at room temperature. The experimental data show a non-trivial increase in conductivity and hole density with a reduced number of layers while maintaining constant field-effect mobility due to the prevalence of electron–phonon scattering. Based on the solution of the 1D Schrödinger–Poisson equation, we find that the observed phenomena are a direct consequence of non-negligible interlayer coupling, which in turn causes a local redistribution of free charge carriers towards the central layers. Our data show that due to the electrostatic conditions at the flake surfaces, a naturally protected 2D hole gas can be encapsulated in flakes as high as 10 nm, which preserves the bulk-like bandgap and effective carrier masses due to the electrostatic environment.
CRIS-Team Scopus Importer:2023-04-14